Analysis and Evolution of Environmental Law in Ecuador with the Constitution of 2008 and its Relation to Political Marketing in the Good Way of Living - Alcívar Trejo, Carlos; Albert Márquez, José J.; Murillo Mena, Ambar; Alvarado Porras, Francisco Marcelo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article is a review and reflection of the new elements of rights and laws, applied to the principle of justice and sovereignty, but above all in the demonstration that law as a science once again allows us to conceive that as a science it evolves and must be modified according to the new conducts that the State and society require, such is the case of the constitutional recognition that this type of rights have. In the last decades, human beings have evidenced that the way in which they interact with nature is causing serious consequences to the ecosystems that compose it. In the past, these consequences were not yet evident and, therefore, the environmental awareness that exists today did not exist. Therefore, it is necessary to analyze and reflect on certain conditions of this right in Ecuador.